Early Discharge versus 6-hour Observation in Mild Traumatic Brain Injury with a Normal Brain CT Scan in a Tertiary Center - Gautam, Subodh; Ghimire, Anisha; Bist, Aayush (Journal of Nepalgunj Medical College, 2025)
Introduction: Mild traumatic brain injury is a common condition presenting to emergency departments, often managed with a period of observation.Aims: To compare the outcomes between early discharge and a 6-hour observation period in mild traumatic brain injury patients with normal brain CT scans.Methods: A prospective observational study was conducted on patients with mild Traumatic brain injury and normal CT scans at Nepalgunj Medical College, Kohalpur, Banke from August-October, 2025. A total of 82 patients presenting to the emergency department with clinical features of mild traumatic brain injury were enrolled and divided into two groups: Group A (Patients discharged early within 2 hours) and Group B (Patients observed in the emergency department for six hours before discharge). Parameters such as post discharge complications, re-admission, neurological deterioration and patient satisfaction were recorded and analyzed using SPSS version 25.Results: The mean age of the participants was 31.33±18.09 years, with 68.3% male patients. No significant differences were found in the baseline characteristics such as mechanism of injury, or duration of loss of consciousness between the two groups. Revisit rates to the emergency department within 7 days were similar between the groups. No patients in either group required neurological intervention or hospitalization after discharge.Conclusion: Our findings suggested that early discharge is equally safe, with no significant differences in post-discharge complications, neurological deterioration, or patient satisfaction compared to a 6-hour observation period.